Про опис локального стану капілярного-пористих та щільно упакованих зернистих матеріалів в процесі сушіння. Частина 1 - Гайвась, Б.І. (Моделювання та інформаційні технології, 2010)
The paper is devoted to studying nonequilibrium thermal, mechanical and diffusive processes in porous media. On the basis of principles of nonreversible processes thermodynamics the state equations are constueted for three-phase multicomponent porous bodies taking into account chemical and interphase transformations. It allows to investigate the processes on the bose of experimental data and with allowance for changes of parameters of both porosity and moisture saturation of body.